Modeling of submerged membrane bioreactor process for wastewater treatment - Lee, Y; Cho, J; Seo, Y; Lee, JW; Ahn, KH (ELSEVIER SCIENCE BV, 2002)
In this study, a mathematical model has been developed for the submerged membrane bioreactor (SMBR) combining the activated sludge model No.1 (ASM1) with a membrane fouling model. The ASM1 was modified to take account into biological characteristics of the SMBR process, and the resistance-in-series model was integrated into the modified ASM 1 to describe membrane fouling. Four additional 1st-order linear differential equations were newly established to describe the fate of soluble microbial products (SMP) and its effects on membrane fouling. Using the model developed here, one can easily predict not only effluent quality but also membrane fouling behavior during the SMBR process. From numerical experiments, F/M ratio and SRT are found to be critical factors controlling SMP concentration in reactor. It also appears that SMP plays an important role in membrane fouling and effluent quality as well. The model developed in this study would provide a useful tool in optimizing operation conditions as well as design parameters for a SMBR system.
Keywords: SOLUBLE MICROBIAL PRODUCTS; ACTIVATED-SLUDGE PROCESS; EXTRACELLULAR POLYMERS; SMP; SYSTEM